Деревна рослинність старовинних парків – пам’яток садово-паркового мистецтва загальнодержавного значення у Сумській області - Klimenko, Y.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The historical data on Kiyanitski and Trostyanetski parks and plans of trees arrangement in these objects are cited. Partial replacement of oak plantations by seedlings and tendencies of improverishment of taxonomic composition and supplement of oaks by ashes are observed.